p–x Data of (Acetic Acid + Water) at T = (412.6, 443.2, 483.2) K - Roman-Ramirez, Luis A.; Leeke, Gary A. (American Chemical Society, 2016)
Experimental – data were measured for the (acetic acid + water) system at the temperatures of (412.6, 443.2 and 483.2) K between the pressures of 196 kPa and 1902 kPa over the entire range of concentrations. Experiments were carried out in a static-analytical equipment with quantitative analysis by GC. The experimental data were correlated with the Perturbed-Chain Statistical Associating Fluid Theory considering two association sites for acetic acid and four association sites for water.